Enhancing Financial Capability and Inclusion in the Philippines : A Demand-Side Survey - World Bank Group (World Bank, Washington, DC, 2016)
In response to a request of the Bangko Sentral ng Pilipinas (BSP) and as part of a broader engagement on enhancing financial consumer protection and education in the Philippines, the World Bank has implemented a financial capability survey. Financial inclusion, financial literacy and consumer protection are important priorities for the BSP and the Philippines government. Consumer protection and education are critical elements in building an inclusive financial system and BSP seeks to identify sustainable methods of delivering financial education through effective partnerships. The proposed survey constitutes a key diagnostic tool that aims to guide BSP on the models for delivering financial education and to set quantifiable and concrete targets. This financial capability survey is the first in the Philippines and one of the very first in the East Asia and Pacific Region (EAPF). The key findings and recommendations presented in this report cover 3 main areas: 1. Financial Inclusion, 2. Financial Capability, and 3. Financial Consumer Protection. The remaining chapters are structured as follows. Chapter 1 explores the financial inclusion landscape in the Philippines. Chapter 2 gives an overview of Filipinos' levels of financial capability, in particular about their financial knowledge, attitudes and behaviors. The last chapter investigates if the products which financially included individuals use are effectively meeting their needs.